Analyzing the medical use of cannabis for cancer patients: a critical perspective - Patel, Rushin; Patel, Mrunal; Patel, Zalak; Kavani, Himanshu; Patel, Darshil; Shaikh, Safia (International Journal Of Community Medicine And Public Health, 2024)
The utilization of cannabis in oncology presents a multifaceted approach to addressing the complex challenges associated with cancer treatment. With roots tracing back to ancient medicinal practices, cannabis contains numerous compounds, including cannabinoids like tetrahydrocannabinol (THC) and cannabidiol (CBD), that interact with the body’s endocannabinoid system. These interactions offer potential therapeutic benefits, ranging from antiemetic and analgesic effects to the inhibition of cancer growth processes. While clinical evidence supports the efficacy of cannabinoids in managing symptoms and enhancing the quality of life for cancer patients, caution is warranted due to potential interactions with conventional medications. Understanding the mechanisms of action, optimal administration routes, and potential side effects is crucial for integrating cannabis into personalized cancer care plans. By navigating these considerations thoughtfully, medical practitioners can harness the therapeutic potential of cannabis to complement traditional cancer treatments and improve patient outcomes in the field of oncology.